Regulatory T cells, damage-associated molecular patterns, and myeloid-derived suppressor cells in bronchoalveolar lavage fluid interlinked with chronic obstructive pulmonary disease severity - Beata Brajer-Luftmann, MD, PhD; Mariusz Kaczmarek, Professor; Agata Nowicka, MD, PhD; Marta Stelmach-Mardas, Professor; Magdalena Wyrzykiewicz, MSc; Senan Yasar, MD; Tomasz Piorunek, Professor; Jan Sikora, Professor; Halina Batura-Gabryel, Professor (Medicine, 2022)
Abstract. The role of regulatory T cells (Tregs), damage-associated molecular patterns (DAMPs), and myeloid-derived suppressor cells (MDSCs) in the mechanism of innate and adaptive immune responses in chronic obstructive pulmonary disease (COPD) is not well understood. Evaluating the presence of Tregs in the bronchoalveolar lavage fluid (BALF) and peripheral blood in patients with COPD, and assessment of the relationship between Tregs, MDSCs, and DAMPs as factors activating innate and adaptive immune responses. Description of the association between immune and clinical parameters in COPD. Thirty-one patients with COPD were enrolled. Clinical parameters (forced expiratory volume in one second [FEV1], forced vital capacity, total lung capacity [TLC], diffusion capacity of carbon monoxide, and B-BMI, O-obstruction, D-dyspnea, E-exercise [BODE]) were assessed. Tregs and MDSCs were investigated in the BALF and blood using monoclonal antibodies directly conjugated with fluorochromes in flow cytometry. The levels of defensin (DEF2), galectin-1 (Gal-1), galectin-3 (Gal-3), galectin-9 (Gal-9), heat shock protein-27 (HSP27), and surfactant protein A were assessed via sandwich enzyme-linked immunosorbent assay. The percentage of Tregs was significantly higher in the blood than in the BALF, in contrast to the mean fluorescence intensity of forkhead box P3 (FoxP3). Significant associations were observed between Tregs and HSP27 (r = 0.39), Gal-1 (r = 0.55), Gal-9 (r = −0.46), and MDSCs (r = −0.50), and between FoxP3 and Gal-1 (r = −0.42), Gal-3 (r = −0.39), and MDSCs (r = −0.43). Tregs and clinical parameters, including FEV1%pred (r = 0.39), residual volume (RV)%pred (r = −0.56), TLC%pred (r = −0.55), RV/TLC (r = −0.50), arterial oxygen saturation (r = −0.38), and arterial oxygen pressure (r = −0.39) were significantly correlated. FoxP3 was significantly interlinked with RV/TLC (r = −0.52), arterial oxygen pressure (r = 0.42), and BODE index (r = −0.57). The interaction between innate and adaptive immune responses in patients with COPD was confirmed. The expression of Tregs in BALF may have prognostic value in patients with COPD. The conversion of immune responses to clinical parameters appears to be associated with disease severity.